Palladium-based composite material and preparation method and application thereof
By assembling palladium-based bimetallic nanoparticles in situ on ZIF-8 porous material, the problem of poor hydrogen sensing performance of existing palladium-based bimetallic nanoparticles materials is solved, and the palladium-based composite material has excellent hydrogen sensing performance and humidity resistance at room temperature.
Patent Information
- Application Number
- CN202311370340.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
The existing palladium-based bimetallic nanoparticles have poor sensing performance on hydrogen, and the preparation method is complicated and the product size is large.
A palladium-based composite material is used, which contains ZIF-8 porous material and palladium-based bimetallic nanoparticles loaded on ZIF-8 porous material. Through one-step synthesis method and in-situ assembly method, palladium-based bimetallic nanoparticles are prepared uniformly dispersed in the porous material ZIF-8 pores.
The palladium-based composite material has excellent hydrogen sensing performance and humidity resistance at room temperature, simplifying the preparation process, and the palladium-based bimetallic nanoparticles have a small size and fast response time.
Smart Images

Figure CN119859767A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen sensing materials, and in particular to a palladium-based composite material and a preparation method and application thereof. Background Art
[0002] At room temperature (RT), palladium (Pd) can react reversibly with H2 to catalyze the dissociation of hydrogen into hydrogen atoms, thereby forming palladium hydride (PdHx) with a higher resistivity than Pd. Quantitative detection of H2 is achieved by detecting the resistance signal based on the Pd sensor. However, poor hydrogen sensing response and slow reaction kinetics are often observed for single Pd metal, and even the response and recovery speed of hydrogen sensors based on nanoscale Pd-based hydrogen-sensitive materials are still insufficient.
[0003] The main preparation methods of palladium-based nanoparticles are electrodeposition, template method and chemical reduction method. The electrodeposition method has disadvantages such as poor repeatability and impure product ingredients, while the template method requires processes such as early template preparation or later template removal, and the operation is cumbersome; in comparison, the chemical reduction method is simple to operate, has good repeatability, and can obtain products with a single morphology and uniform size. At present, the seed method, that is, the two-step method, is commonly used to prepare palladium-based nanoparticles. Not only does it require the pre-preparation of palladium-based nanoparticles with a certain morphology as seeds, but it is also necessary to add a morphology control agent in the subsequent reaction to guide or limit the growth of specific crystal faces, and then continue to grow on the basis of the original morphology to obtain palladium-based nanoparticles with different crystal faces. The method is cumbersome and the size of the bimetallic nanoparticles is large. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems that the existing palladium-based bimetallic nanoparticle materials have poor hydrogen sensing performance, and the existing palladium-based bimetallic nanoparticle materials have complicated preparation methods and the prepared bimetallic nanoparticles have large sizes, and to provide a palladium-based composite material and its preparation method and application. The palladium-based composite material provided by the present invention has excellent hydrogen sensing performance and humidity resistance at room temperature; the present invention can synthesize palladium-based bimetallic nanoparticles in one step, and the preparation method of the palladium-based composite material is simple and easy to operate.
[0005] In order to achieve the above-mentioned objectives, the present invention provides a palladium-based composite material on the one hand, which comprises a ZIF-8 porous material and palladium-based bimetallic nanoparticles loaded on the ZIF-8 porous material, wherein the palladium-based bimetallic nanoparticles comprise palladium element and transition metal element.
[0006] Preferably, the molar ratio of the ZIF-8 porous material, the palladium element and the transition metal element is 1-10:1:0.1-1.
[0007] Preferably, the specific surface area of the palladium-based composite material is 1000-2000m2 / g, preferably 1500-2000m 2 / g.
[0008] Preferably, the particle size of the palladium-based bimetallic nanoparticles is 5-20 nm, preferably 7-10 nm.
[0009] Preferably, the transition metal element is selected from one or more of Group VIII, Group IB and Group IIB metal elements.
[0010] Preferably, the transition metal element is selected from one or more of copper, nickel, cobalt and zinc.
[0011] A second aspect of the present invention provides a method for preparing a palladium-based composite material, the method comprising the following steps:
[0012] S1, mixing a palladium precursor, a transition metal precursor, a morphology control agent, a reducing agent and a surfactant, and reacting them to obtain palladium-based bimetallic nanoparticles;
[0013] S2. reacting 2-methylimidazole, a zinc source, a solvent and the palladium-based bimetallic nanoparticles.
[0014] Preferably, the molar ratio of the palladium precursor, the transition metal precursor, the morphology control agent and the reducing agent is: 1:0.1-1:0.5-1:4-20.
[0015] Preferably, in step S1, the reaction conditions include: reaction temperature of 100-250°C, preferably 180-220°C; reaction time of 5-25 hours, preferably 8-15 hours.
[0016] Preferably, in step S1, the surfactant is selected from one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, polyvinylpyrrolidone, cetylpyridinium chloride, sodium dodecylbenzenesulfonate and cis-oleyl primary amine.
[0017] Preferably, in step S1, the palladium precursor is selected from one or more of palladium acetylacetonate, palladium chloride and palladium nitrate.
[0018] Preferably, in step S1, the transition metal precursor is a transition metal salt of acetylacetonate.
[0019] Preferably, in step S1, the transition metal in the transition metal precursor is selected from one or more of group VIII, group IB and group IIB metal elements.
[0020] Preferably, in step S1, the transition metal precursor is selected from one or more of copper acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate and zinc acetylacetonate.
[0021] Preferably, in step S1, the morphology control agent is a chloride salt.
[0022] Preferably, in step S1, the morphology control agent is selected from one or more of ferric chloride, sodium chloride and potassium chloride.
[0023] Preferably, in step S1, the reducing agent is selected from one or more of ascorbic acid, sodium borohydride and sodium hypophosphite.
[0024] Preferably, in step S1, the mixing treatment conditions include: the mixing treatment method is ultrasonic treatment; the mixing treatment time is 30-100 minutes.
[0025] Preferably, in step S2, the molar ratio of the 2-methylimidazole to the zinc source is 13-18:1.
[0026] Preferably, in step S2, the molar ratio of the palladium-based bimetallic nanoparticles to the zinc source is 1:4-10.
[0027] Preferably, in step S2, the reaction conditions include: reaction temperature of 0-50°C, preferably 0-5°C; reaction time of 1-8h, more preferably 3-5h.
[0028] Preferably, in step S2, the zinc source is zinc nitrate.
[0029] Preferably, in step S2, the solvent is selected from one or more of methanol, N,N-dimethylformamide, ethanol, n-heptane and water.
[0030] The third aspect of the present invention provides a palladium-based composite material prepared by the method described above.
[0031] A fourth aspect of the present invention provides a hydrogen sensor, wherein the hydrogen sensor contains the palladium-based composite material described above.
[0032] A fifth aspect of the present invention provides an application of the palladium-based composite material described above as a hydrogen-sensitive material.
[0033] A sixth aspect of the present invention provides an application of the palladium-based composite material described above in a hydrogen sensing performance test.
[0034] The palladium-based composite material provided by the present invention contains palladium-based bimetallic nanoparticles and a specific porous material ZIF-8. On the one hand, palladium and transition metal cooperate with each other, and the bimetallic nanoparticles show more excellent sensing performance through the synergistic effect between the metals; on the other hand, the porous material ZIF-8 can not only filter out interfering gases that affect hydrogen response, but also has a high specific surface area, and can accelerate the response time of hydrogen at room temperature through the pre-adsorption effect on hydrogen; thirdly, the palladium-based bimetallic nanoparticles are uniformly dispersed in the porous material ZIF-8 (which can be observed by TEM), so that the composite material has excellent hydrogen sensing performance, and the porous material ZIF-8 can prevent water vapor from entering the porous material ZIF-8, so that the composite material has excellent humidity resistance.
[0035] The present invention adopts a liquid phase reduction method, and does not need to prepare palladium nanoparticles in advance as seed crystals. It only needs to mix a bimetallic precursor, a morphology control agent, a reducing agent and a surfactant, and heat the reaction to obtain palladium-based bimetallic nanoparticles with a specific morphology (spherical, which can be observed by TEM). Then, the palladium-based bimetallic nanoparticles and the porous material ZIF-8 are in situ assembled in the liquid phase. The palladium-based bimetallic nanoparticles can be evenly dispersed in the pores of the porous material to prevent further agglomeration. The prepared composite material has excellent hydrogen sensing performance and humidity resistance at room temperature.
[0036] In summary, the present invention adopts a one-step synthesis method and an in-situ assembly method, and the palladium-based bimetallic nanoparticles obtained are uniformly dispersed in the pores of the porous material ZIF-8 and are small in size. They have a fast response time to hydrogen and have strong mechanical strength, chemical stability, and humidity resistance. They can quickly detect and respond to hydrogen leakage in the environment at room temperature to ensure their safe use. At the same time, the method for preparing the hydrogen-sensitive material is simple and environmentally friendly, and the raw materials are inexpensive. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The XRD pattern (a) of the material prepared in Example 1; the XPS pattern (b) ; the TEM pattern (c) ; the SEM pattern and the EDS pattern (d) ;
[0038] Figure 2 is the resistance variation curve of the material prepared in Example 1 over time (298K);
[0039] Figure 3 is the resistance variation curve of the material prepared in Comparative Example 1 over time (298K);
[0040] Figure 4 is the resistance variation curve of the material prepared in Comparative Example 2 over time (298K);
[0041] Figure 5This is the resistance change curve of the material prepared in Example 1 with humidity (298K). DETAILED DESCRIPTION
[0042] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0043] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0044] The first aspect of the present invention provides a palladium-based composite material, which contains a ZIF-8 porous material and palladium-based bimetallic nanoparticles loaded on the ZIF-8 porous material, wherein the palladium-based bimetallic nanoparticles contain palladium elements and transition metal elements.
[0045] The palladium-based composite material provided by the invention contains palladium-based bimetallic nanoparticles and a specific porous material ZIF-8. The hydrogen sensing performance of the palladium-based composite material can be improved through the synergistic effect between palladium and transition metals. The porous material ZIF-8 provides a suitable loading matrix for the palladium-based bimetallic nanoparticles. The palladium-based bimetallic nanoparticles are uniformly dispersed in the porous material ZIF-8, which can improve the stability and hydrogen sensing performance of the palladium-based composite material. Meanwhile, the porous material ZIF-8 can filter out interfering gases (interfering gases can be carbon monoxide, water vapor, hydrogen sulfide, methane, etc.) that affect hydrogen response. The porous material ZIF-8 has a high specific surface area, and can accelerate the response time of hydrogen at room temperature through the pre-adsorption effect on hydrogen. The porous material ZIF-8 can prevent water vapor from entering the porous material ZIF-8, thereby improving the humidity resistance of the palladium-based composite material.
[0046] In a preferred embodiment, the molar ratio of the ZIF-8 porous material, the palladium element and the transition metal element is 1-10: 1: 0.1-1. The ratio of the ZIF-8 porous material, the palladium element and the transition metal element is limited to this range, and the ZIF-8 porous material has a fast response time to hydrogen, high mechanical strength, and excellent chemical stability and humidity resistance. If there is too much ZIF-8 porous material, the conductivity of the composite material is poor, and if there is too little ZIF-8 porous material, the humidity resistance of the composite material is poor; the ratio of the palladium element and the transition metal element should be appropriate. If there is too much palladium element, the cost of the composite material becomes high, and if there is too little palladium element, the hydrogen sensing performance is affected.
[0047] The palladium-based composite material of the present invention has a high specific surface area. Preferably, the specific surface area of the palladium-based composite material is 1000-2000m 2 / g, preferably 1500-2000m 2 / g.
[0048] In the present invention, the particle size of the palladium-based bimetallic nanoparticles is relatively small and is evenly distributed in the pores of the porous material ZIF-8. Preferably, the particle size of the palladium-based bimetallic nanoparticles is 5-20 nm, more preferably 7-10 nm.
[0049] In some embodiments, the transition metal element is selected from one or more of the metal elements of Group VIII, Group IB and Group IIB. In a preferred embodiment, the transition metal element is selected from one or more of copper, nickel, cobalt and zinc; the synergistic effect of palladium and these metal elements can further improve the hydrogen sensing performance. Further preferably, the transition metal element is copper.
[0050] A second aspect of the present invention provides a method for preparing a palladium-based composite material, the method comprising the following steps:
[0051] S1, mixing a palladium precursor, a transition metal precursor, a morphology control agent, a reducing agent and a surfactant, and reacting them to obtain palladium-based bimetallic nanoparticles;
[0052] S2. reacting 2-methylimidazole, a zinc source, a solvent and the palladium-based bimetallic nanoparticles.
[0053] In the method described in the present invention, a palladium precursor, a transition metal precursor, a morphology control agent, a reducing agent and a surfactant are synthesized by a one-step method to obtain palladium-based bimetallic nanoparticles, and then a palladium-based composite material in which the palladium-based bimetallic nanoparticles are uniformly dispersed in the pores of the porous material ZIF-8 and the size of the palladium-based bimetallic nanoparticles is relatively small is obtained by in-situ assembly.
[0054] In a preferred embodiment, the molar ratio of the palladium precursor, the transition metal precursor, the morphology control agent and the reducing agent is: 1:0.1-1:0.5-1:4-20.
[0055] The reaction in step S1 of the present invention is carried out at a relatively high temperature to obtain palladium-based bimetallic nanoparticles. In some embodiments, in step S1, the reaction temperature can be 100-250°C, and the reaction time can be 5-25 hours. In a preferred embodiment, in step S1, the reaction temperature is 180-220°C; the reaction time is 8-15 hours; controlling the reaction temperature within this preferred range can obtain palladium-based bimetallic nanoparticles with smaller and uniform sizes, which can improve the hydrogen sensing performance of the palladium-based composite material.
[0056] In the present invention, the surfactant is also a solvent. The amount of the surfactant used is not limited, as long as the palladium precursor, transition metal precursor, morphology control agent, and reducing agent solvent can be mixed evenly. In the present invention, due to the use of a surfactant, a one-step synthesis method can be used to obtain palladium-based bimetallic nanoparticles.
[0057] In some embodiments, in step S1, the surfactant may be selected from one or more of CTAB (cetyltrimethylammonium bromide), CTAC (cetyltrimethylammonium chloride), PVP (polyvinylpyrrolidone), CPC (cetylpyridinium chloride), SDBS (sodium dodecylbenzenesulfonate) and oleylamine (cis-oleyl primary amine). In a preferred embodiment, the surfactant is oleic acid; using oleic acid as a surfactant can obtain palladium-based bimetallic nanoparticles with smaller and uniform sizes.
[0058] In the present invention, the palladium precursor can be a conventional choice in the art. In some embodiments, in step S1, the palladium precursor is selected from one or more of palladium acetylacetonate, palladium chloride and palladium nitrate; preferably, the palladium precursor is palladium acetylacetonate.
[0059] In the method of the present invention, the role of the transition metal precursor is to provide a transition metal that has a synergistic effect with palladium. In some embodiments, in step S1, the transition metal precursor is a transition metal salt of acetylacetonate. In other embodiments, in step S1, the transition metal in the transition metal precursor is selected from one or more of the metal elements of Group VIII, Group IB and Group IIB.
[0060] In a preferred embodiment, in step S1, the transition metal precursor is selected from one or more of copper acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate and zinc acetylacetonate; further preferably, the transition metal precursor is copper acetylacetonate.
[0061] In order to make the size of the obtained palladium-based bimetallic nanoparticles smaller by the one-step synthesis method, in step S1, the morphology control agent is a chloride salt. The chloride salt can be a conventional choice in the art, as long as it can provide chloride ions; preferably, in step S1, the morphology control agent is selected from one or more of ferric chloride, sodium chloride and potassium chloride, more preferably ferric chloride. The form of the ferric chloride is not limited, and it can be anhydrous ferric chloride or ferric chloride hexahydrate.
[0062] In the present invention, the reducing agent may be a conventional choice in the art. In some embodiments, in step S1, the reducing agent is selected from one or more of ascorbic acid, sodium borohydride and sodium hypophosphite, preferably ascorbic acid.
[0063] In a preferred embodiment, in step S1, the mixing treatment is carried out by ultrasonic treatment; ultrasonic mixing can mix the raw materials more evenly. In a preferred embodiment, the mixing treatment time is 30-100 minutes.
[0064] Step S1 of the present invention may also include: after the reaction of step S1 is completed, a colloidal product is obtained by centrifugation, and then washed three times with a mixture of acetone, ethanol and cyclohexane, and then dried at 60° C. in vacuum for 24 hours to obtain a palladium-based bimetallic nanoparticle product.
[0065] In the present invention, in order to prepare the ZIF-8 porous material, the ratio of the 2-methylimidazole to the zinc source needs to be appropriate. In some embodiments, in step S2, the molar ratio of the 2-methylimidazole to the zinc source is 13-18:1, preferably 15:1.
[0066] In order to ensure that the content of palladium-based bimetallic nanoparticles in the palladium-based composite material is not too small, the palladium-based bimetallic nanoparticles are distributed more evenly in the ZIF-8 porous material. In a preferred embodiment, in step S2, the molar ratio of the palladium-based bimetallic nanoparticles to the zinc source is 1:4-10.
[0067] In some embodiments, in step S2, the reaction temperature may be 0-50°C, and the reaction time may be 1-8h. In order to stabilize the structure of the ZIF-8 porous material and thereby improve the structural stability and chemical stability of the palladium-based composite material, in a preferred embodiment, in step S2, the reaction temperature is 0-5°C, and the reaction time is 3-5h.
[0068] In the present invention, the zinc source can be any conventional choice in the art, as long as it can provide zinc ions. In a preferred embodiment, in step S2, the zinc source is zinc nitrate.
[0069] In the present invention, in step S2, the solvent may be a conventional choice in the art. In some embodiments, in step S2, the solvent may be selected from one or more of methanol, N,N-dimethylformamide, ethanol, n-heptane and water.
[0070] Step S2 of the present invention may further include: after the reaction of step S2 is completed, washing with methanol, then collecting the product by centrifugation, and drying under vacuum at 60° C. for 24 hours.
[0071] The third aspect of the present invention provides a palladium-based composite material prepared by the method described above.
[0072] Preferably, the palladium-based composite material contains a ZIF-8 porous material and palladium-based bimetallic nanoparticles loaded on the ZIF-8 porous material, wherein the palladium-based bimetallic nanoparticles contain palladium elements and transition metal elements.
[0073] Preferably, the molar ratio of the ZIF-8 porous material, the palladium element and the transition metal element is 1-10:1:0.1-1.
[0074] Preferably, the specific surface area of the palladium-based composite material is 1000-2000m 2 / g, preferably 1500-2000m 2 / g.
[0075] Preferably, the particle size of the palladium-based bimetallic nanoparticles is 5-20 nm, preferably 7-10 nm.
[0076] Preferably, the transition metal element is selected from one or more of copper, nickel, cobalt and zinc.
[0077] A fourth aspect of the present invention provides a hydrogen sensor, wherein the hydrogen sensor contains the palladium-based composite material described above.
[0078] In one embodiment, the palladium-based composite material can be coated on a sensor substrate, dried, and aged to obtain a hydrogen sensor.
[0079] A fifth aspect of the present invention provides an application of the palladium-based composite material described above as a hydrogen-sensitive material.
[0080] A sixth aspect of the present invention provides an application of the palladium-based composite material described above in a hydrogen sensing performance test.
[0081] The present invention will be described in detail below by way of examples, but the protection scope of the present invention is not limited thereto. In the following examples, unless otherwise specified, all reagents used are commercially available.
[0082] The examples are used to illustrate the preparation process of the palladium-based composite material.
[0083] Example 1
[0084] (1) 8 mg of acetylacetonate palladium, 6.9 mg of acetylacetonate copper, 5.4 mg of ferric chloride hexahydrate, and 35.6 mg of ascorbic acid were dissolved in 5 mL of oleylamine and ultrasonically treated for 60 min, wherein the molar ratio of acetylacetonate palladium: acetylacetonate copper: ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7. The obtained mixture was heated in an oil bath at 200°C for 12 hours, and a colloidal product was obtained by centrifugation. The colloidal product was washed three times with a mixture of acetone, ethanol and cyclohexane, and vacuum dried at 60°C for 24 hours to obtain palladium-copper bimetallic nanoparticles.
[0085] (2) 1.1 g of 2-methylimidazole and 0.265 g of Zn(NO3)2·6H2O were dissolved in 50 mL of methanol solution, 9 mg of palladium-copper bimetallic nanoparticles were weighed and mixed with the mixture, and the mixture was stirred and reacted at 0°C (in an ice-water bath) for 4 h. The product was washed twice with methanol and collected by centrifugation, and dried in vacuum at 60°C for 24 h to obtain a palladium-based composite material, wherein the molar ratio of 2-methylimidazole to Zn(NO3)2·6H2O was 16:1, and the molar ratio of palladium-copper bimetallic nanoparticles to Zn(NO3)2·6H2O was 1:8.
[0086] The XRD, XPS, TEM, SEM and EDS images of the palladium-based composite material prepared in Example 1 are as follows: Figure 1 As shown, (a) XRD pattern; (b) XPS pattern; (c) TEM pattern; (d) SEM pattern and EDS pattern.
[0087] It can be seen from the XRD diagram that the composite material has characteristic peaks of ZIF-8 at 2θ of 7.4°, 10.45°, 12.8°, 14.76°, 16.5° and 18.08°, and characteristic peaks of PdCu nanoparticles at 2θ of 41.7° and 47.8°, which proves that after the PdCu nanoparticles are composited with ZIF-8, the crystal structures of ZIF-8 and PdCu are retained.
[0088] It can be seen from the XPS graph that the Pd element in the composite material is mainly metallic Pd 0 (corresponding to peaks at 335.5 and 340.6 eV), and a small amount of oxidized Pd 2+ (corresponding to peaks at 336.8 and 342.0 eV) exist, and Pd is not observed 4+ The corresponding peaks exist, which is mainly because the PdCu nanoparticles exist inside ZIF-8, slowing down the oxidation rate of Pd, so Pd mainly exists as zero-valent Pd.
[0089] It can be seen from the TEM images that PdCu nanoparticles with uniform sizes are dispersed in the porous material ZIF-8.
[0090] It can be seen from the SEM and EDS images that the ZIF-8 rhombic dodecahedron structure contains two elements, Pd and Cu, and the Pd and Cu elements are in the form of highly dispersed particles, which further confirms the successful preparation of PdCu@ZIF-8.
[0091] Example 2
[0092] The method of Example 1 was followed, except that 6.9 mg of copper acetylacetonate was replaced with 6.77 g of nickel acetylacetonate, wherein the molar ratio of palladium acetylacetonate: nickel acetylacetonate: ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7.
[0093] Example 3
[0094] The method of Example 1 was followed, except that 6.9 mg of copper acetylacetonate was replaced with 6.83 g of cobalt acetylacetonate, wherein the molar ratio of palladium acetylacetonate:cobalt acetylacetonate:ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7.
[0095] Example 4
[0096] The method of Example 1 was followed, except that 6.9 mg of copper acetylacetonate was replaced with 6.95 g of zinc acetylacetonate, wherein the molar ratio of palladium acetylacetonate: zinc acetylacetonate: ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7.
[0097] Example 5
[0098] The method of Example 1 was followed, except that 8 mg of palladium acetylacetonate was replaced with 16 mg of palladium acetylacetonate, wherein the molar ratio of palladium acetylacetonate: copper acetylacetonate: ferric chloride hexahydrate and ascorbic acid was 1:0.5:0.385:3.85.
[0099] Example 6
[0100] The method of Example 1 was followed, except that 5.4 mg of ferric chloride hexahydrate was replaced with 3.5 mg of ferric chloride hexahydrate, wherein the molar ratio of acetylacetonate palladium: acetylacetonate copper: ferric chloride hexahydrate and ascorbic acid was 1:1:0.5:7.7.
[0101] Example 7
[0102] The method of Example 1 was followed, except that 35.6 mg of ascorbic acid was replaced with 22.9 mg of ascorbic acid, wherein the molar ratio of acetylacetonate palladium: acetylacetonate copper: ferric chloride hexahydrate: ascorbic acid was 1:1:0.77:4.95.
[0103] Example 8
[0104] The method of Example 1 was followed, except that 5 mL of oleylamine was replaced with 15 mL of oleylamine.
[0105] Example 9
[0106] The method of Example 1 was followed, except that heating at 100° C. in an oil bath was used instead of heating at 200° C. in an oil bath.
[0107] Example 10
[0108] The method of Example 1 was followed, except that 9 mg of palladium-copper bimetallic nanoparticles were replaced with 15 mg of palladium-copper bimetallic nanoparticles, and the molar ratio of palladium-copper bimetallic nanoparticles to Zn(NO3)2·6H2O was 1:4.8.
[0109] Embodiment 11
[0110] The method of Example 1 was followed, except that the stirring reaction at 0°C (in an ice-water bath) for 4 h was replaced by stirring the reaction at 25°C for 4 h.
[0111] Example 12
[0112] The method of Example 1 was followed, except that the stirring reaction at 0°C (in an ice-water bath) for 1 h was replaced with the stirring reaction at 0°C (in an ice-water bath) for 4 h.
[0113] Embodiment 13
[0114] The method of Example 1 was followed, except that oleylamine was replaced with CTAB in step (1).
[0115] Comparative Example 1
[0116] Only palladium nanoparticles are prepared according to the method of Example 1, and the specific process includes the following steps:
[0117] 8 mg of acetylacetonate palladium, 5.4 mg of ferric chloride hexahydrate, and 35.6 mg of ascorbic acid were dissolved in 5 mL of oleylamine and ultrasonically treated for 60 min, wherein the molar ratio of acetylacetonate palladium: ferric chloride hexahydrate and ascorbic acid was 1:0.77:7.7. The resulting mixture was heated at 200°C in an oil bath for 12 hours, and the colloidal product was collected by centrifugation, washed three times with a mixture of acetone, ethanol and cyclohexane, and vacuum dried at 60°C for 24 hours to obtain palladium nanoparticles.
[0118] Comparative Example 2
[0119] Only palladium-copper bimetallic nanoparticles are prepared according to the method of Example 1, and the specific process includes the following steps:
[0120] 8 mg of acetylacetonate palladium, 6.9 mg of acetylacetonate copper, 5.4 mg of ferric chloride hexahydrate, and 35.6 mg of ascorbic acid were dissolved in 5 mL of oleylamine and ultrasonically treated for 60 min, wherein the molar ratio of acetylacetonate palladium: copper acetylacetonate: ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7. The resulting mixture was heated at 200°C in an oil bath for 12 hours, and the colloidal product was collected by centrifugation, washed three times with a mixture of acetone, ethanol and cyclohexane, and vacuum dried at 60°C for 24 hours to obtain palladium-copper bimetallic nanoparticles.
[0121] Comparative Example 3
[0122] Only palladium-nickel bimetallic nanoparticles are prepared according to the method of Example 2, and the specific process includes the following steps:
[0123] 8 mg of acetylacetonate palladium, 6.77 g of acetylacetonate nickel, 5.4 mg of ferric chloride hexahydrate, and 35.6 mg of ascorbic acid were dissolved in 5 mL of oleylamine and ultrasonically treated for 60 min, wherein the molar ratio of acetylacetonate palladium: acetylacetonate nickel: ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7. The resulting mixture was heated at 200°C in an oil bath for 12 hours, and the colloidal product was collected by centrifugation, washed three times with a mixture of acetone, ethanol and cyclohexane, and vacuum dried at 60°C for 24 hours to obtain palladium-nickel bimetallic nanoparticles.
[0124] Comparative Example 4
[0125] Only palladium-cobalt bimetallic nanoparticles are prepared according to the method of Example 3, and the specific process includes the following steps:
[0126] 8 mg of acetylacetonate palladium, 6.83 g of acetylacetonate cobalt, 5.4 mg of ferric chloride hexahydrate, and 35.6 mg of ascorbic acid were dissolved in 5 mL of oleylamine and ultrasonically treated for 60 min, wherein the molar ratio of acetylacetonate palladium: acetylacetonate cobalt: ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7. The resulting mixture was heated at 200°C in an oil bath for 12 hours, and the colloidal product was collected by centrifugation, washed three times with a mixture of acetone, ethanol and cyclohexane, and vacuum dried at 60°C for 24 hours to obtain palladium-cobalt bimetallic nanoparticles.
[0127] Comparative Example 5
[0128] Only palladium-zinc bimetallic nanoparticles are prepared according to the method of Example 4, and the specific process includes the following steps:
[0129] 8 mg of acetylacetonate palladium, 6.95 g of acetylacetonate zinc, 5.4 mg of ferric chloride hexahydrate, and 35.6 mg of ascorbic acid were dissolved in 5 mL of oleylamine and ultrasonically treated for 60 min, wherein the molar ratio of acetylacetonate palladium: zinc acetylacetonate: ferric chloride hexahydrate and ascorbic acid was 1:1:0.77:7.7. The resulting mixture was heated at 200°C in an oil bath for 12 hours, and the colloidal product was collected by centrifugation, washed three times with a mixture of acetone, ethanol and cyclohexane, and vacuum dried at 60°C for 24 hours to obtain palladium-zinc bimetallic nanoparticles.
[0130] Comparative Example 6
[0131] The method of Example 1 was followed, except that 5.4 mg of ferric chloride hexahydrate was not added.
[0132] Comparative Example 7
[0133] The method of Example 1 was followed, except that 35.6 mg of ascorbic acid was not added.
[0134] Comparative Example 8
[0135] The method of Example 1 is followed, except that 6.9 mg of copper acetylacetonate is not added in step (1). The specific process includes the following steps:
[0136] (1) 8 mg of acetylacetonate palladium, 5.4 mg of ferric chloride hexahydrate, and 35.6 mg of ascorbic acid were dissolved in 5 mL of oleylamine and ultrasonically treated for 60 min, wherein the molar ratio of acetylacetonate palladium: ferric chloride hexahydrate and ascorbic acid was 1:0.77:7.7. The obtained mixture was heated in an oil bath at 200° C. for 12 h, and a colloidal product was obtained by centrifugation. The colloidal product was washed three times with a mixture of acetone, ethanol and cyclohexane, and vacuum dried at 60° C. for 24 h to obtain palladium nanoparticles.
[0137] (2) 1.1 g of 2-methylimidazole and 0.265 g of Zn(NO3)2·6H2O were dissolved in 50 mL of methanol solution, 9 mg of palladium nanoparticles were weighed and mixed with the mixture, and the mixture was stirred and reacted at 0°C (in an ice-water bath) for 4 h. The product was washed twice with methanol and collected by centrifugation, and dried in vacuum at 60°C for 24 h to obtain a palladium-based composite material, wherein the molar ratio of 2-methylimidazole to Zn(NO3)2·6H2O was 16:1, and the molar ratio of palladium nanoparticles to Zn(NO3)2·6H2O was 1:10.
[0138] Comparative Example 9
[0139] The method of Example 1 was followed, except that 5 mL of 0.02 M hydrochloric acid solution was used instead of oleylamine.
[0140] Test Example 1
[0141] The contents of the various components in the materials prepared in the examples and comparative examples were tested using an inductively coupled plasma mass spectrometer (ICP-MS). The results are shown in Table 1.
[0142] Table 1
[0143]
[0144]
[0145] Test Example 2
[0146] The particle sizes of the metal nanoparticles in the materials prepared in the examples and comparative examples were tested using a transmission electron microscope (TEM). The results are shown in Table 2.
[0147] Table 2
[0148]
[0149]
[0150] Test Example 3
[0151] The hydrogen sensing performance of the materials prepared in the examples and comparative examples was tested in the Elite gas sensing test system (CGS-8). The test method was as follows: the materials obtained in the examples and comparative examples were placed in a closed 500 mL chamber, a hydrogen-air mixed gas (hydrogen 1 volume %) was introduced, and freely diffused to the entire closed chamber, and the resistance change curve was measured at room temperature (298k) over time to calculate the response time (t 90 ), and the average value of 5 measurements was calculated. The test results are shown in Table 3. The resistance variation curves of the materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 over time are shown in Table 3. Figure 2 , Figure 3 and Figure 4 shown.
[0152] Table 3
[0153]
[0154]
[0155] from Figure 2-4 It can be seen that the response time (t 90 ) are 6s, 42s and 24s respectively.
[0156] Test Example 4
[0157] The humidity resistance of the material prepared in Example 1 was tested, wherein the resistance change curve of the material prepared in Example 1 with humidity is as follows: Figure 5 shown.
[0158] The humidity resistance of the material prepared in Example 1 was tested in the Elite gas-sensitive test system (CGS-8). The test method was as follows: the material obtained in Example 1 was placed in a closed 500mL chamber with humidity of 20% RH, 40% RH, 60% RH and 80% RH, respectively, and a hydrogen-air mixed gas (hydrogen 1 volume %) was introduced to diffuse freely throughout the closed chamber. The resistance change curve was measured at room temperature (298k) over time, and the response time (t 90 ).
[0159] from Figure 5 It can be seen that the response time (t 90 ) changes in a range of less than 5%, indicating that the material prepared in Example 1 has excellent humidity resistance.
[0160] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A palladium-based composite material, characterized in that: The palladium-based composite material contains a ZIF-8 porous material and palladium-based bimetallic nanoparticles loaded on the ZIF-8 porous material, wherein the palladium-based bimetallic nanoparticles contain palladium elements and transition metal elements.
2. The palladium-based composite material according to claim 1, characterized in that The molar ratio of the ZIF-8 porous material, the palladium element and the transition metal element is 1-10:1:0.1-1.
3. The palladium-based composite material according to claim 1 or 2, characterized in that: The specific surface area of the palladium-based composite material is 1000-2000m 2 / g, preferably 1500-2000m 2 / g.
4. The palladium-based composite material according to any one of claims 1 to 3, characterized in that: The particle size of the palladium-based bimetallic nanoparticles is 5-20 nm, preferably 7-10 nm.
5. The palladium-based composite material according to any one of claims 1 to 3, characterized in that: The transition metal element is selected from one or more of Group VIII, Group IB and Group IIB metal elements; Preferably, the transition metal element is selected from one or more of copper, nickel, cobalt and zinc.
6. A method for preparing a palladium-based composite material, characterized in that: The method comprises the following steps: S1, mixing a palladium precursor, a transition metal precursor, a morphology control agent, a reducing agent and a surfactant, and reacting them to obtain palladium-based bimetallic nanoparticles; S2. reacting 2-methylimidazole, a zinc source, a solvent and the palladium-based bimetallic nanoparticles.
7. The method according to claim 6, characterized in that The molar ratio of the palladium precursor, the transition metal precursor, the morphology control agent and the reducing agent is: 1:0.1-1:0.5-1:4-20.
8. The method according to claim 6 or 7, characterized in that: In step S1, the reaction conditions include: reaction temperature of 100-250°C, preferably 180-220°C; reaction time of 5-25 hours, preferably 8-15 hours.
9. The method according to any one of claims 6 to 8, characterized in that: In step S1, the surfactant is selected from one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, polyvinylpyrrolidone, cetylpyridinium chloride, sodium dodecylbenzenesulfonate and cis-oleyl primary amine.
10. The method according to any one of claims 6 to 9, characterized in that: In step S1, the palladium precursor is selected from one or more of palladium acetylacetonate, palladium chloride and palladium nitrate.
11. The method according to any one of claims 6 to 10, characterized in that: In step S1, the transition metal precursor is an acetylacetonate transition metal salt; Preferably, in step S1, the transition metal in the transition metal precursor is selected from one or more of group VIII, group IB and group IIB metal elements; Preferably, in step S1, the transition metal precursor is selected from one or more of copper acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate and zinc acetylacetonate.
12. The method according to any one of claims 6 to 11, characterized in that: In step S1, the morphology control agent is a chloride salt; Preferably, in step S1, the morphology control agent is selected from one or more of ferric chloride, sodium chloride and potassium chloride.
13. The method according to any one of claims 6 to 12, characterized in that: In step S1, the reducing agent is selected from one or more of ascorbic acid, sodium borohydride and sodium hypophosphite.
14. The method according to any one of claims 6 to 13, characterized in that: In step S1, the mixing treatment conditions include: the mixing treatment method is ultrasonic treatment; the mixing treatment time is 30-100 minutes.
15. The method according to any one of claims 6 to 14, characterized in that: In step S2, the molar ratio of the 2-methylimidazole to the zinc source is 13-18:
1.
16. The method according to any one of claims 6 to 15, characterized in that: In step S2, the molar ratio of the palladium-based bimetallic nanoparticles to the zinc source is 1:4-10.
17. The method according to any one of claims 6 to 16, characterized in that: In step S2, the reaction conditions include: reaction temperature of 0-50°C, preferably 0-5°C; reaction time of 1-8h, more preferably 3-5h.
18. The method according to any one of claims 6 to 17, characterized in that: In step S2, the zinc source is zinc nitrate; Preferably, in step S2, the solvent is selected from one or more of methanol, N,N-dimethylformamide, ethanol, n-heptane and water.
19. A palladium-based composite material prepared by the method according to any one of claims 6 to 18.
20. A hydrogen sensor, characterized in that: The hydrogen sensor contains the palladium-based composite material according to any one of claims 1 to 5 or the palladium-based composite material according to claim 19.
21. Use of the palladium-based composite material according to any one of claims 1 to 5 or the palladium-based composite material according to claim 19 as a hydrogen-sensitive material.
22. Use of the palladium-based composite material according to any one of claims 1 to 5 or the palladium-based composite material according to claim 19 in a hydrogen sensing performance test.